Improving Community Performance Through Salary, Work Environment, And Workforce Training In Sunggal District, Deli Serdang - Darmilisani Darmilisani; Dian Yulis Wulandari; Yohanes Parsaoran Tamba (Proceeding of The International Conference on Business and Economics, 2024)
A person who achieves the best performance will be appreciated by the company with good rewards. And with poor performance, will get punishment. The extent to which they can give their best performance depends on how they want to improve their competence and willingness (motivation) to do their best work. The purpose of this study is to improve community performance through salary, work environment, and labor training in Sunggal District, Deli Serdang. This research is a qualitative descriptive study using the literature review method through library studies based on previous research journals. The results of this study explained that several things can improve community performance in Sunggal District, Deli Serdang Regency such as the amount of income or salary, a supportive work environment, and job training needed to improve skills and knowledge at work. To achieve an improved quality of community performance, it is necessary to do several things, namely reviewing the amount of salary as a reward to the community and paying overtime hours reasonably by the overtime time used, reviewing the workforce training program which is considered less attractive, unclear direction and objectives, so that interest in participating in the workforce training program is low. And open the widest possible space for outstanding people to get promoted to a higher career level.